2022
DOI: 10.1111/cns.13789
|View full text |Cite
|
Sign up to set email alerts
|

Results from a multicenter, randomized, double‐blind, placebo‐controlled study of repository corticotropin injection for multiple sclerosis relapse that did not adequately respond to corticosteroids

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…No serious AEs or deaths were reported. It was concluded that Acthar was effective for patients with MS that was not responsive to corticosteroid treatment (Table 4 ) [ 52 ].…”
Section: Clinical Studies Of Acthar: 2014–2022mentioning
confidence: 99%
“…No serious AEs or deaths were reported. It was concluded that Acthar was effective for patients with MS that was not responsive to corticosteroid treatment (Table 4 ) [ 52 ].…”
Section: Clinical Studies Of Acthar: 2014–2022mentioning
confidence: 99%
“…1 Controlled clinical trials have shown that RCI increases recovery rates and improves disability scores in patients with acute MS relapse. 25 In the multicenter, randomized, double-blind, placebo-controlled, parallel-group OPTIONS trial, 35…”
Section: Clinical Benefitsmentioning
confidence: 99%
“…Clinical studies have demonstrated the efficacy of Acthar in patients with inflammatory diseases that are refractory to glucocorticoid treatment (Askanase et al, 2020 ; Baughman et al, 2017 ; Fleischmann et al, 2020 ; Wynn et al, 2022 ). Acthar also can directly inhibit B cell proliferation and antibody production (Olsen et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%